The Pedagogy of Suffering: Four Fragments - Jardine, David W.; McCaffrey, Graham; Gilham, Christopher (Paideusis, 2014)
This paper is a collection of small, formal and informal writings and is part of the early groundwork we have been doing together on the topic of the pedagogy of suffering, a phrase that has certainly given pause to many colleagues we have spoken to. We are trying to understand and articulate how and why suffering can be pedagogical in character and how it is often key to authentic and meaningful acts of teaching and learning. We are exploring threads from both the hermeneutic tradition and from Buddhism, in order to decode our understandable rush to ameliorate suffering at every turn and to consider every instance of it as an error to be avoided at all costs. We also look to these traditions to begin to formulate how a pedagogy that turns away from suffering suffers a great loss, and how a pedagogy that turns towards suffering can become a locale of great teaching and learning, great wisdom and grace.